Piccole zone di simmetria - Bresciani Califano, Mimma (Firenze University Press, 2022)
If it intends to enhance awareness and to stimulate intellectual and cultural maturity, literature cannot ignore – and when it survives over time does not ignore – the great conquests of philosophical thought and the fundamental stages marked by the progress of scientific knowledge. A scientific result and a poetic result both represent an internally-ordered fragment of reality which moves and stirs us by the intrinsic beauty of the image that it evokes and its significance at the level of meaning. Both scientific and literary languages, each in its own way, tend to the decodification and representation of the external world. Imagination, intuition and rationality come together in creativity, in the construction of scientific models and of literary styles.